2017
DOI: 10.4236/jdm.2017.74022
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dyslipidemia and Glycated Haemoglobin in Gestational Diabetes Mellitus

Abstract: Background: GDM is a condition where there is an onset of carbohydrate intolerance during pregnancy. In this condition many changes will take place in carbohydrate metabolism and other metabolic pathways especially in lipid metabolism. These metabolic changes associated with insulin resistance and dyslipidemia. We have aim to study the association between dyslipidemia and glycated haemoglobin. Materials and Methods: The study was conducted in 80 pregnant women of rural population of Puducherry in two groups. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Furthermore, Khan et al (22) found that the value of FBG was 112 ± 8.70 mg/dL in GDM groups compared to 87 ± 6.90 mg/ dL in healthy pregnant women (P < 0.001). Contrarily, Lenin et al (19) indicated no significant difference in FBG value among non-GDM and GDM groups among an Indian population. They reported an FBG measure of 72.45± 7.23 mg/dL and 74.3 ± 9.18 mg/dL (P = 0.23) in the 2 groups, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, Khan et al (22) found that the value of FBG was 112 ± 8.70 mg/dL in GDM groups compared to 87 ± 6.90 mg/ dL in healthy pregnant women (P < 0.001). Contrarily, Lenin et al (19) indicated no significant difference in FBG value among non-GDM and GDM groups among an Indian population. They reported an FBG measure of 72.45± 7.23 mg/dL and 74.3 ± 9.18 mg/dL (P = 0.23) in the 2 groups, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Hyperlipidemia typically occurs during normal pregnancy and alterations in lipid profile is known to occur in GDM (11). Significantly elevated levels of HbA1c in GDM and its relation to lipid profile were reported by several researchers (19,22,23). McGrowder at al indicated HbA1c concentration was higher in women with GDM (P = 0.001); in addition, they found that TC and triglycerides were significantly high in these women (P=0.039 for TC and P = 0.033 for TG).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fasting Lipid profile and GDM have been shown to be the important predic-Journal of Biosciences and Medicines tors for maternal metabolic disturbances including dyslipidemia, hypertension and cardiovascular disease [12]. Moreover, pre-pregnancy BMI was found to have a far greater effect on IR in pregnancy in Asian women than Caucasians [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore serum lipid profile is important in the assessment of blood glucose levels. The abnormalities of carbohydrate metabolism observed in GDM may affect other metabolic pathways especially lipid metabolism [12]. IR which is one of the primary defects in majority of GDM presumed to have important relationship with dyslipidaemia in pregnancy and future cardio-metabolic risk [13].…”
Section: Introductionmentioning
confidence: 99%